Enantioselective synthesis of (S)-alpha-arylpropionic acids via pd-catalyzed kinetic resolution of benzylic alcohols - Thakur, V. V.; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2005)
A convenient synthetic route for the synthesis of three (S)-alpha-propionic acids, (S)-naproxen (90% ee), (S)-ibuprofen (82% ee) and (S)-phenylpropioilic acid (92% ee) is described. Pd-catalyzed oxidative kinetic resolution of the corresponding benzylic alcohols is used as a key step to introduce stereogenicity into the molecule.